The Effect of Auto Gate Systems on The Traveler Profiling System at Soekarno-Hatta International Airport - Martadireja, Okky Pratama; Romdendine, Muhammad Fahrury (Innovative: Journal Of Social Science Research, 2024)
The growing numbers of international flights have resulted in the improvement of immigration processes at the airports. Therefore, self-service biometric gates have been developed to guarantee more speed and security at the border. In this paper, the authors evaluate the effects of implementing auto gate systems at Soekarno-Hatta International Airport, specifically looking into the effect of operational efficiencies, privacy, and data security. This study uses a qualitative approach to literature analysis. The author uses previous studies, Government papers, and industry documents to identify the mechanisms that facilitate effective implementation and acceptance of these systems and their relationship to privacy and data security issues. Implementation of the proper auto gate systems might ease immigration processes and encourage traveling around the world, but addressing internal aspects like perception, data safety, and even human beings will always be vital. The findings from this analysis recommend an increase in the data protection models in place, enhancing the accuracy of the systems and making the procedures more open.